Analysis of the Methods of Covering the Working Surfaces of the Parts with Vacuum Ion-Plasmas and the Change of Surface Layers (Eurasian Scientific Herald, 2022)
This article discusses proposals and recommendations for increasing the duration of nitriding to obtain a layer thickness by studying the composition and structure of steel and contrast materials using vacuum-ion-plasma coating methods when restoring details of working surfaces.